2011
DOI: 10.1097/opx.0b013e31821ffbd4
|View full text |Cite
|
Sign up to set email alerts
|

Quantified Histopathology of the Keratoconic Cornea

Abstract: Purpose The present study systematically investigated and quantified histopathological changes in a series of keratoconic (Kc) corneas utilizing a physiologically formulated fixative to not further distort the already distorted diseased corneas. Methods Twelve surgically removed Kc corneal buttons were immediately preserved and processed for light and transmission electron microscopy using an established corneal protocol. Measurements were taken from the central cone and peripheral regions of the host button… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 38 publications
6
51
1
5
Order By: Relevance
“…31,32 Compared to an age-matched control group, the keratoconic cornea was shown to be thinner across the full width of the cornea, but the difference between normal and keratoconic corneas became smaller toward the limbus. 32 Histopathology demonstrated that the pathological changes seen peripheral to the Fleischer's ring were the same as those observed centrally in the cone, but, again, to a lesser degree.…”
Section: Discussionmentioning
confidence: 96%
“…31,32 Compared to an age-matched control group, the keratoconic cornea was shown to be thinner across the full width of the cornea, but the difference between normal and keratoconic corneas became smaller toward the limbus. 32 Histopathology demonstrated that the pathological changes seen peripheral to the Fleischer's ring were the same as those observed centrally in the cone, but, again, to a lesser degree.…”
Section: Discussionmentioning
confidence: 96%
“…The present data used the same way of grading the degree of KC as Emre and coworkers [16] (i.e., k-values), however, the larger number of KC eyes included by Emre et al may also explain the narrower anterior chamber angle in severe cases of KC found in their study as compared to the present data. It was recently demonstrated that the peripheral cornea was affected by this disease [11,12]. However, both these studies found the peripheral cornea was affected to a lesser degree than the tissue within the Fleischer ring; presumably these peripheral changes were not sufficient to alter the geometry of the angle.…”
Section: Discussionmentioning
confidence: 94%
“…With KC patients angle estimates using the traditional von Herick's technique may not provide accurate assessment and gonioscopy may provoke undesired corneal trauma and discomfort. The latter is especially the case with the KC diseased corneal structure where the epithelial adhesion apparatus is greatly affected [11]. An evaluation of the anterior chamber angle in KC subjects is most frequently screened during biomicroscopy using van Herick's technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Es besteht ein Verlust von stromalen Kollagen-Lamellen und eine gestörte Ausrichtung der Kollagenfibrillen. Verminderte Keratozytendichte zeigt sich insbesondere im zentralen vorderen Stroma [50]. [35,36].…”
Section: Pathologieunclassified